Crni Bombarder - Bajić, Darko (Yugoslavia : FIVET ; Kikinda ; RTV Beograd, 1992)
Set during the presidential elections in the near-future Belgrade, the story follows popular radio-speaker Crni (Black) who tries to stir up spirits with his rocking anti-establishment radio show “The Black Bomber.” One night he meets Luna, a passionate punk-rock singer who wants to go to London and tries to convince her to stay here and follow her artistic vision. After an incident at radio-station when an armed madman barges in the studio during Crni’s show and insults a president, Crni is sent on temporary leave. Still he refuses to give up his “mission.” He continues to broadcast revolutionary programs from a van, inviting the youth to go out to the streets and protest, with the police constantly on his trail and Luna desperately trying to get to him. He finally succeeds in instigating riots, but gets arrested and ends up talking with the president who, surprisingly, turns out to be quite a liberal, interested in his opinions and willing to give him his own radio show. He manages to meet with Luna before she leaves for London and in a finale has a vision of both of them flying over the town.
Keywords: Fiction films